1991
DOI: 10.1302/0301-620x.73b3.1670451
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and fracture-dislocation of the hip

Abstract: Of 54 patients with posterior dislocations of the hip of type I and type II (Stewart and Milford 1954), 47 were followed for a mean period of 6.7 years (2 to 11). Of these, 23 had dislocation with minimal lesions of the acetabulum (type I) and 24 had an avulsed dorsocranial fragment (type II). All were reduced by closed methods within six hours. The subsequent treatment of type I dislocations was conservative. At the beginning of the period type II injuries were treated conservatively, but surgery was increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
2
22
1
Order By: Relevance
“…The passengers' mean ages of 33.2 years and age range of 22-52 years are similar to findings of others who have worked on traumatic posterior dislocation of the hip joints and is a reflection of young adults being the age group mostly on the roads (Akiode and Oyelakin, 2003;Jaskulka et al, 1991). It has been shown that when large males adjust their seats forwards, they are t an increased risk of sustaining lower limb injuies (Hill and Boyle, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…The passengers' mean ages of 33.2 years and age range of 22-52 years are similar to findings of others who have worked on traumatic posterior dislocation of the hip joints and is a reflection of young adults being the age group mostly on the roads (Akiode and Oyelakin, 2003;Jaskulka et al, 1991). It has been shown that when large males adjust their seats forwards, they are t an increased risk of sustaining lower limb injuies (Hill and Boyle, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Again, an increased frequency of AVN occurred after delays in reduction greater than this. 2,50 THDs are frequently associated with multiple injuries. 9 Multiple injuries in turn affect a patients general mobility and 4,7 The issue of time to weight-bearing after the reduction of THD has long been contentious, with some authors recommending an extended period of non-weight-bearing in order to allow restoration of blood flow to the femoral head, reducing the risk of AVN.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, traction or prolonged immobilization followed by a long period of nonweight-bearing was recommended. Recent reports have not shown deleterious effects from early mobilization, and several authors have documented that a prolonged nonweight-bearing period does not significantly influence the subsequent development of femoral head osteonecrosis [1,15,16,23].…”
Section: Resultsmentioning
confidence: 99%
“…Instability, loose fragment retention in the hip joint or incomplete reduction precludes a good result. Sahin et al considered fragments outside the immediate weight-bearing zone of the hip to be important also; their study reported satisfactory results, were obtained with a prompt and stable hip reduction regardless of the treatment method [1,16].…”
Section: Discussionmentioning
confidence: 99%